Social integration and substance use: assessing the effects of an early intervention programme for youth. Issue 3 (21st March 2016) - Brand, Amélie; Guillod, Line; Habersaat, Stéphanie; Panchaud, Evelyne; Stéphan, Philippe; Urben, Sébastien
Abstract: Aim: Appropriate social integration has been shown to be a protective factor against substance use among adolescents and associated negative consequences. Promoting social integration through early intervention with adolescents using substances is thus necessary and is the aim of the Identification, Assessment and Follow‐up of Adolescents with Substance Use (in French, Dépistage ‐ évaluation ‐ parrainage d'adolescents consommateurs de substances (DEPART) programme. The present study aimed to describe this programme and its participants from 2009 to 2013 as well as to assess its effects on social integration. Methods: Data from 398 adolescents using substances who attended the DEPART programme were analysed. Results: The results showed that almost 80% of the adolescents admitted to the DEPART programme were boys, with a large proportion using cannabis. Globally, social integration did not increase from admission to discharge from the programme, but a shift was observed for school and professional integration. Additionally, after the intervention, we observed that social integration was more important in younger patients. Conclusions: This study showed that adolescents with problematic substance use mostly consumed soft drugs and that those who were integrated into the DEPART programme at a younger age were more likely to be socially integrated at the end of the programme.